Lessening morbidity and mortality in surgery - Han, Ho-Seong (World Nutrition Journal, 2024)
Surgeons always try to improve outcomes of patients by lessening morbidity and mortality and. Proper plan during perioperative period is essential as nutritional support influence short-term and long-term outcomes in malnourished or undernourished patients.